Maintenance and generalization of skills acquired through picture exchange communication system (PECS) training: a long-term follow-up. (4th July 2019) - Jurgens, Anneke; Anderson, Angelika; Moore, Dennis W.
ABSTRACT: Purpose: To conduct a follow-up assessment of the maintenance of communication skills of a 7-year-old child with autism spectrum disorder, 3 years 7 months post PECS training; and investigate the effects of environmental adaptations on the child's PECS and vocal communications. Methods: An alternating-treatments design enabled comparison of the effects of two treatment conditions (an environmental adaptation to increase need and opportunities for communication, versus a continuation of baseline procedures) on the child's PECS and vocal communications in the child's home. Results: Baseline data demonstrated decreased levels of PECS and vocal communication at follow-up, compared to post PECS training 3 years 7 months prior. The environmental adaptation had no observable effect on the participant's use of PECS, but vocal manding increased in this condition. Conclusion: These results suggest ongoing need for motivating environments with ample opportunities to practice post PECS training. Implications and directions for future research are discussed.